Projections And Problems of Land Registration Through A Complete Systematic Land Registration (Ptsl) Policy (Study At BPN Mataram City) - Yanto, Edi; Sarudi; Sahrul (Faculty of Law, University of Mataram, 2024)
The author can describe the aim of this research as follows: first: To get a complete picture of the projected implementation of land registration through Complete Systematic Land Implementation (PTSL) at BPN Mataram, second: To get a complete picture of the problems faced in implementing the land registration program through Systematic Land Implementation Complete (PTSL) at BPN Mataram. This type of research is normative and empirical legal research that examines legal materials and data. The approaches used are a legislative approach, a conceptual approach and a sociological approach. The technique for collecting legal materials and data is using literature studies and interviews. After the legal materials and data have been identified, the next stage is processing by systematizing them, then reasoning logically and systematically using qualitative descriptive analysis and drawing conclusions deductively. The projected implementation of land registration through Complete Systematic Land Implementation (PTSL) at BPN Mataram is carried out to provide legal certainty and legal protection to land owners and avoid disputes and disputes in the future which is carried out free of charge for the community. This program began in 2017 and will end in 2025. The land plots targeted for 2022, 2023 and 2024 have met each year's target with a total of 2,076 land plots mapped. Problems faced in implementing the land registration program through Complete Systematic Land Implementation (PTSL) at BPN Mataram include internal factors such as the lack of availability of Facilities and Infrastructure and Certificates Issued Before Complete Mapping of the System, while external factors include a lack of community initiative to register, and the community has difficulty in prepare application files and proof of land ownership (Alas Hak).